2018
DOI: 10.3390/bioengineering5030060
|View full text |Cite
|
Sign up to set email alerts
|

Merging Heterocyclic Chemistry and Biocatalysis in One-Pot Processes through Compartmentalization of the Reaction Steps

Abstract: A proof of concept for a one-pot process merging a heterocycle formation by a classical chemical approach at basic conditions with a biocatalytic reduction, running at neutral pH conditions, is reported. A crucial component for this process is the compartmentalization of the single reactions by the use of polydimethylsiloxane thimbles. This process was applied successfully towards an asymmetric synthesis of (S)-2,2,3-trimethyl-1-thia-4-azaspiro[4.4]nonane, leading to excellent enantioselectivities of 99% enant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…Acetophenones varying in substituent and location on the ring were all readily accommodated, including highly lipophilic cases (14 and 19) and for one case bearing ortho-substitution (20). Cyclic ketones such as a Cbz-protected 4-oxoazepane (21), and N-Boc and N-Cbz-protected 3-pyrrolidinones, afforded the corresponding amines (22 and 23) in reasonable yields and, with the exception of 21, high ee's. Enones appeared to present no obstacles to this asymmetric reductive amination to yield allylic amines 12 and 13.…”
Section: Table 1 Screening Of the Aqueous Reaction Medium Involving V...mentioning
confidence: 99%
See 1 more Smart Citation
“…Acetophenones varying in substituent and location on the ring were all readily accommodated, including highly lipophilic cases (14 and 19) and for one case bearing ortho-substitution (20). Cyclic ketones such as a Cbz-protected 4-oxoazepane (21), and N-Boc and N-Cbz-protected 3-pyrrolidinones, afforded the corresponding amines (22 and 23) in reasonable yields and, with the exception of 21, high ee's. Enones appeared to present no obstacles to this asymmetric reductive amination to yield allylic amines 12 and 13.…”
Section: Table 1 Screening Of the Aqueous Reaction Medium Involving V...mentioning
confidence: 99%
“…The especially timely area of chemoenzymatic catalysis features both bio-and chemo-catalysis being done in the same pot. 21 Oftentimes, compartmentalization or other clever approaches are required that enable compatibility, since reagent and solvent issues may prevent both from being used in the same medium. Given that chemocatalysis in water is enabled by designer surfactants, 22,23 24 where TPGS-750-M-aided 1-pot cascades are composed of various classes of chemocatalysis (e.g., Mizoroki-Heck cross-coupling, ring closing metathesis, and olefin metathesis) and biocatalysis (e.g., lipase and esterase).…”
Section: Chemoenzymatic Catalysismentioning
confidence: 99%
“…Das Konzept fi ndet darüber hinaus Anwendung in chemoenzymatischen Reaktionen, z. B. beschrieben durch N. Zumbrägel und H. Gröger für eine Asinger-Multikomponentenreaktion mit einer nachgeschalteten Iminreduktase-katalysierten Reduktion zum fi nalen zyklischen Amin [9].…”
Section: Biokatalyseunclassified
“…Although most of these methods give racemic products [5][6][7], it is noteworthy that Martens, Shibasaki and their coworkers demonstrated that the latter transformation was able to be conducted even in an asymmetric fashion leading to high enantioselectivities for the formation of the resulting α-amino phosphonates [9][10][11]. As a long-lasting challenge for decades, the (enantioselective) reduction of this C-N double bonds of 3-thiazolines leading to the non-cleaved thiazolidine heterocycles (which are a subunit, e.g., in the pharmaceutically important penicillin-type antibiotics) in high conversion and excellent enantiomeric excess was recently realized by conducting the reaction by means of enzyme catalysis (Scheme 1) [12][13][14]. In detail, the reduction is catalyzed by means of an imine reductase and the reduced form of a cofactor (NADPH), which is regenerated in situ by consuming D-glucose as the stoichiometrically required (cheap) reducing agent.…”
Section: Introductionmentioning
confidence: 99%